Family Therapy Around the World : a Festschrift for Florence W. Kaslow. - Nichols, William (Taylor and Francis, 2014)
An international celebration of the work of Florence W. Kaslow! Family Therapy Around the World: A Festschrift for Florence W. Kaslow celebrates the life and work of the distinguished family therapist with an international collection of essays that reflects the dynamic state of clinical practice, research, and theory. Professionals and practitioners from 15 countries honor Dr. Kaslow's pioneering contributions to family therapy and family psychology by offering practical solutions to the real, everyday problems that affect today's world. The essays are varied and extensive, incorporati.